Factors Associated with Knowledge and Practices of Menstrual Hygiene among Adolescent School-Going Girls of Birendranagar Municipality, Surkhet - Bhedi, Sumi Kumari; Khanal, Shankar Prasad (Nepalese Journal of Statistics, 2024)
Background: Menstruation refers to a susceptible period in the life of adolescent girls. Various factors are associated with knowledge and practices of menstrual hygiene among adolescent girls. Objective: To identify the factors associated with knowledge and practices of menstrual hygiene among adolescent school-going girls of Birendranagar Municipality, Surkhet. Materials and Methods: A self-administered questionnaire collected the primary data of 372 adolescent school-going girls using a stratified random sampling technique. The study used both descriptive and inferential statistical analysis. Multiple logistic regression model was used followed by bivariate analysis. The goodness of fit of the model was examined by using the Hosmer-Lemeshow test and the accuracy of fitted model by using Receiver Operating Characteristic (ROC) Curve. Results: The average age (mean ± SE) and the average age (mean ± SE) at menarche of the respondents were 14.62 ± 0.059 years and 12.47 ± 0.049 years respectively. The variables where respondents do not attain program/sessions at school about menstruation before menarche [OR:4.81, 95% CI: (1.36, 16.97), p = 0.015 ], who believed no effect of menstruation on academic performance [OR:0.21, 95% CI: (0.05, 0.84), p = 0.028], the heavy amount of bleeding [OR: 5.73, 95% CI: (1.63, 20.20), p = 0.007] and having restriction i.e. not allowed to sleep in their own room [OR: 6.02, 95% CI: (1.71, 21.24), p = 0.005] were significantly associated with poor knowledge of menstrual hygiene at α = 0.05. The fit of the model is good [H-L ( ) = 5.803, p = 0.446] and the AUC is 85.9%. Likewise, it is found that the poor practices of menstrual hygiene are significant with the reaction of respondents to their first menstruation i.e. emotional disturbance [OR: 13.34, 95% CI = (1.55, 114.99)] and having restriction i.e. not allowed to enter the kitchen during menstruation [OR: 3.86, 95% CI = (1.71, 8.65)] at α = 0.05. The fit of the model is good [H-L ( ) = 3.238, p = 0.778] and the AUC is 72.2%. Conclusion: Students not attending sessions about menstruation and traditional barriers such as not allowed to sleep in their own room and not believing the effect of this on academic performance are highly responsible to the poor knowledge of menstrual hygiene. Emotional disturbances and restricting girls from kitchen during menstruation also contribute to poor hygiene practices. Addressing these issues within families can improve menstrual hygiene knowledge and practices.